2021
DOI: 10.3390/app11073085
|View full text |Cite
|
Sign up to set email alerts
|

Grazing Incidence Small-Angle Neutron Scattering: Background Determination and Optimization for Soft Matter Samples

Abstract: Grazing incidence small-angle neutron scattering (GISANS) provides access to interfacial properties, e.g., in soft matter on polymers adsorbed at a solid substrate. Simulations in the frame of the distorted wave Born approximation using the BornAgain software allow to understand and quantify the scattering pattern above and below the sample horizon, in reflection and transmission, respectively. The small-angle scattering from the interfacial layer, visible around the transmitted beam, which might contribute al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…and horizontal instrument axes. et al, 2007;Ruderer et al, 2012;Kyrey et al, 2021) but, to date, has not been comprehensively reported on for the study of magnetic nanostructures in low-dimensional condensed matter systems.…”
Section: Near-surface Sansmentioning
confidence: 99%
“…and horizontal instrument axes. et al, 2007;Ruderer et al, 2012;Kyrey et al, 2021) but, to date, has not been comprehensively reported on for the study of magnetic nanostructures in low-dimensional condensed matter systems.…”
Section: Near-surface Sansmentioning
confidence: 99%
“…4(a)]. Transmission scattering is especially severe for GISANS (Kyrey et al, 2021). Scattering below the horizon is thus a sign of background contributions associated with the direct beam.…”
Section: Q Ymentioning
confidence: 99%
“…The last technical paper in this issue focuses on the impact of SANS background in the case of grazing incidence SANS (GISANS) [7]. GISANS has been developed into a method in its own right over the last decades; however, it still remains closely linked to SANS, both scientifically and technologically.…”
mentioning
confidence: 99%